Dos perspectivas frente al lenguaje lógico de Frege: una revisión crítica de la lectura tradicional de la conceptografía (2020)
In this dissertation, two interpretations of the artificial language that Frege introduced in Concept-Script (1879) and developed in Basic Laws of Arithmetic (1893/1903) are assessed as readings of Frege's texts. On the one hand, Michael E. Dummet's traditional interpretation is considered in relation to his conviction that the concept-script is a notational variant of modern-day logic languages. On the other hand, the interpretation of the Canadian philosopher Danielle Macbeth is examined scrutinizing her belief that the concept-script is not such a notational-variant insofar as it is not designed to trace truth-conditions, but to exhibit inferential contents. The dissertation's main thesis is that, in the light of Macbeth's interpretation, Dummett's reading is compelling only to the extent that Frege is believed to hold an atomistic understanding of the structure of a thought, that is, of the structure of that which in a sentence is relevant from a logical point of view...